Analysis of the Influence of Behavioral Bias on Investment Decisions of Young Investors in Surabaya - Herman Saputro; Ira Wikartika (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the effect of the illusion of control, financial literacy and herding bias on the investment decision making of young investors in Surabaya. The population in this study are capital market investors who are domiciled in Surabaya. The sampling technique used in this study was a purposive sampling technique with the results of sample calculations obtained by a total of 95 respondents. This study used quantitative method with data collection techniques using questionnaires which were distributed to respondents in the city of Surabaya which were then analyzed using SmartPLS 4. The results of this study indicate that there is a positive effect on financial literacy on investment decisions for young investors in Surabaya, while the illusion of control and herding bias variables have no effect on investment decisions on young investors in Surabaya.